A Literature Review on Social Innovation and Community Flood Preparedness in Alignment with SFDRR and SDG: Recommendations for Dam Failure Flood Risk Management - Khanm T.; Kaman Z.K.; Samsuddin S.A.B. (International Information and Engineering Technology Association, 2025)
In response to the escalating challenges posed by climate change, the United Nations (UN) proactively formulated the Sendai Framework for Disaster Risk Reduction (SFDRR-2015-2030) as a comprehensive strategy for disaster risk management (DRM). This framework delineates four priority action objectives, seven global targets, and a set of guiding principles aimed at mitigating the impact of disasters. Notably, each of the seven SFDRR targets is intricately linked with the Sustainable Development Goals (SDG-2030). Given that natural disasters, such as floods, continue to hinder a country's social and economic progress, achieving long-term development becomes challenging. Both frameworks prioritize initiating and investing in innovation, involving all of society's stakeholders, to build a risk-informed and people-centered disaster-resilient society. However, a research gap exists regarding the relationship between Social Innovation (SI) and disaster risk preparedness. To address this, the present study conducts an in-depth literature review and content analysis focused on SI and flood preparedness. The study also aims to offer strategic recommendations for adopting SI to improve preparedness against dam-related flood risks, aligning with SFDRR targets and SDGs-2030. The study's findings are valuable for academia, policymakers, flood risk management agencies, at-risk communities, and stakeholders. By shedding light on the role of SI in flood risk preparedness, the research contributes to existing knowledge and enhances understanding of SI in the context of disaster risk management. ?2024 The authors.